42.3: Light Leakage Study of the Curved ADS Mode LCDs. Issue 1 (June 2015) - You, Jaegeon; Zhao, Weili; Jung, Chulgyu; Qin, Guangkui; Kim, Kiman; Yang, Yafeng; Wu, Zhongbao; Wang, Xinxing
Abstract : Light leakage mechanism of curved ADS mode LCDs was studied by simulation and experiments; it was founded that the glass got an optical retardation because upper/bottom glass of the panel got a residual stress, under the effect of the stress optical coefficient, and then combining with LC layer's optical retardation, the light leakage occurred under cross polarizer. In this paper, simulation and experimental result was compared, and was proven to be perfect similar.